Safety of Metformin Therapy in Patients with Type 2 Diabetes Living on an Oxygen-Deficient Plateau, Tibet, China - Lv, Xuemei; Ren, Qian; Zhou, Lingli; Geng, Yanyan; Song, Jia; Mina, A; Puchi, Basang; Yang, Senlin; Meng, Shuyou; Yang, Lihui (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background In the general population, the absolute risk of lactic acidosis in patients treated with metformin appears to be low. However, in the Tibetan plateau, an extreme oxygen-deficient environment, there are no data available concerning the safety of metformin. The aim of our study is to assess the safety of metformin in people of the plateau area.Methods We conducted an observational cross-sectional study in Tibet. All the 166 subjects were divided into two groups: T2DM+metformin group and T2DM group. Clinical characteristics as well as lactate levels were measured in all subjects. The association between lactate, metformin use, FBG, HbA1c, eGFR, and other potential predictors was evaluated.Results A total of 166 subjects were enrolled in this study. Average age was 51.7±12.3 years, and the percentage of male participants was 67%. The median level of lactate was 1.89 (1.35–2.91) mmol/L in all the subjects. The mean (±SD) lactate concentration in patients treated with metformin, versus those who were not, was 2.35±1.42 vs 2.29±1.65 mmol/L, respectively (mean difference 0.06 mmol/L, 95% CI: −0.48–0.60, P=0.556). FBG was significantly higher in the high lactate group than in the low lactate group (12.1±4.1 vs. 10.5±4.0 mmol/L, P=0.018). Similarly, HbA1c level was also significantly higher in the high lactate group than in the low lactate group (12.3±2.6 vs. 11.0±3.0%, P=0.008).Conclusions In the oxygen-deficient Tibetan plateau, lactate concentration among patients on metformin was not significantly different from patients without metformin. The level of lactate was significantly associated with FBG and HbA1c levels.
Keywords: lactate; metformin; type 2 diabetes